A transmissive, spectrum-splitting concentrating photovoltaic module for hybrid photovoltaic-solar thermal energy conversion. (1st November 2016) - Xu, Qi; Ji, Yaping; Riggs, Brian; Ollanik, Adam; Farrar-Foley, Nicholas; Ermer, Jim H.; Romanin, Vince; Lynn, Pete; Codd, Daniel; Escarra, Matthew D.
Highlights: A spectrum splitting, transmissive CPV module is shown in a hybrid PV-thermal system. Module has conversion efficiency exceeding 43.5% for above bandgap (in-band) light. Module cooling (<110 °C) is maintained with high transmission of IR light (>75%). System is designed for dispatchable electricity or industrial process heat generation. Abstract: A spectrum splitting, transmissive concentrating photovoltaic (tCPV) module is proposed and designed for a hybrid photovoltaic-solar thermal (PV/T) system. By utilizing III–V triple junction solar cells with bandgaps of 2.1 eV/1.7 eV/1.4 eV, ultraviolet (UV) and visible light will be absorbed and converted to electricity, while infrared (IR) light will pass through and be captured by a solar thermal receiver and stored as heat. The stored thermal energy may be dispatched as electricity or process heat, as needed. According to the numerical analysis, the tCPV module can perform with overall power conversion efficiency exceeding 43.5% for above bandgap (in-band) light under a standard AM1.5D solar spectrum, under an average concentration ratio of 400 suns. Passive and active cooling methods, keeping cells below 110 °C, are also investigated and discussed, indicating that a transparent active cooling design could improve the CPV module efficiency by around 1% (absolute), relative to a passive design, by reducing the maximum cell working temperature by around 16 °C. Furthermore, cost analysis shows that installation cost of around 1.9/W–2.2/W could be reached for the tCPV based PV/T system, which shows a competitive economic advantage compared to a more conventional PV with battery system.